Answer:
x = 6
Step-by-step explanation:
Since KN is the perpendicular bisector, that means ∠KNM = ∠KNQ = 90° and MN = NQ so therefore, since they are right triangles, ΔKNM ≅ ΔKNQ because of HL. Therefore, KM = KQ by CPCTC so:
5x - 3 = 3x + 9
2x = 12
x = 6
The number -33 divisors are:
D(-33) = {-33, -11, -3, -1, 1, 3, 11, 33}
a × b = -33
<u>1) -33 × 1 = -33 ⇒ Sum is: -33 + 1 = -32</u>
2) -11 × 3 = -33 ⇒ Sum is: -11 + 3 = -8
3) -3 × 11 = -33 ⇒ Sum is: -3 + 11 = 8
4) -1 × 33 = -33 ⇒ Sum is: -1 + 33 = 32
<u>5) 1 × (-33) = -33 ⇒ Sum is: 1 + (-33) = 1 - 33 = -32</u>
6) 3 × (-11) = -33 ⇒ Sum is: 3 + (-11) = 3 - 11 = -8
7) 11 × (-3) = -33 ⇒ Sum is: 11 + (-3) = 11 - 3 = 8
8) 33 × (-1) = -33 ⇒ Sum is: 33 + (-1) = 33 - 1 = 32
<h2>The least possible sum of a and b is -32</h2>
to 1) and to 5)
<h3>
Answer:</h3>
- A. x = -2
- B. (-2, -3), (-3, -1)
- C. x = 0
<h3>
Step-by-step explanation:</h3>
Part A. The solution is represented by the point at which the graphs intersect: (-2, -3). The x-value that makes p(x) = f(x) is x = -2.
___
Part B. The point found in Part A is one solution to f(x). The graph shows the line has a slope of -2, so another point will be 1 to the left and 2 up: (-3, -1). So, two solutions are ...
... (-2, -3) and (-3, -1)
___
Part C. The graphs of p(x) and g(x) intersect at the point (0, 2). This means
... p(0) = g(0) = 2
So, x = 0 is the solution to the equation p(x) = g(x).